Efeito do treinamento periodizado ondulatório vs bloco atr sobre os biomarcadores de estresse, desempenho físico e composição corporal em nadadores amadores - SILVA, Vinicius Lourenço José da (2019)
The objective of the present study was to investigate the effect of undulating periodized versus block training on biomarkers of stress, body composition and physical performance in amateur swimmers. A total of 23 university amateur swimmers were randomly allocated to the groups: 1) block (GB, n = 8), three are female and five males; age: 21.5 ± 2.3 years; height: 171 ± 0.5 cm; body mass: 74.7 ± 8.5 kg; 2) undulating (GO, n = 8) six are females and two males; age: 24.3 ± 6.5 years; height: 165 ± 0.8 cm; body mass: 64.6 ± 9.2 kg, and; 3) control (GC, n = 7), three are females and four males; age: 26.1 ± 8.2 years; height: 171 ± 0.1 cm; body mass: 70.1 ± 10.5 kg. GB and GO performed 12 weeks of dryland resistance training following their respective periodizations, while the GC maintained pool training. There was no significant change (p> 0.05) for testosterone and cortisol concentrations at the end of the intervention and among the groups tested. (P = 0.05, ETA: 54%), maximum strength and mean velocity of the swim (Vm) (p = 0.01; ETA: 37%) increased significantly for Block Group and Undulating Group. IMM presented a direct and moderate correlation with Vm (r = 0.41, p = 0.04). The periodization models tested were satisfactory for improving physical performance and body composition without affecting stress biomarkers in amateur athletes.